Antioxidant and Antimicrobial Activity of Citrus Limetta: Life Sciences-Microbiology - Kumari, Sony; Jyoti Koch, Pranab; Islam, Muzaharul; Rahman, Anisur; Sikdar, Mamoni; Debbarma, Rahel; Nasrin, Nahid (International Journal of Life Science and Pharma Research, 2024)
One of the most common fruit crops grown in tropical and subtropical areas is Citrus limetta. Upon processing, about40-47% percent of the fruit’s non-edible mass is discarded as waste that impacts the environment. The aromatic compounds calledessential oils (EOs) are concentrated in oil glands found in leaves, flowers, and fruit peels. The study’s primary objective was toevaluate the biological activity of fresh and heated peels extracted essential oil from Citrus limetta (CLEO). The study emphasizedthe determination of bioactive compounds from the CLEO antioxidant and antimicrobial activity assessment. CLEO’s main volatilecomponent was D-Limonene in both oils, with RA (%) values of 44.14 and 77.50 in fresh and heated peel oil, respectively. Theantioxidant activity was comparable to the standard used for ascorbic. The activity (%) reached its highest (83±1.53%) at theconcentration of of100μL/mL for fresh peel oil, which is higher than the heated peel oil. Comparative antimicrobial activity wasdetermined to assess the effects of CLEO against ten bacterial pathogens, which implies that seven pathogens were significantlysensitive against heated oil. The current findings suggest that CLEO could be an impressive natural source with significant potentialto show good biological activity in both fresh and treated forms. A complex composition with approximately 20 components inCitrus limetta essential oil has been scientifically proven beneficial in aromatherapy, medications, beverages, food color enhancers,and aromatic-nature infusions for personal health care.